Neocolonialism and science diplomacy: lessons learned from the field and the way forward - Dajani, Rana; Bayoumi, Rasha; Flowe, Heather; Rockowitz, Sarah; Stevens, Laura; Awad, Abdullah (Frontiers in Public Health, 2024)
To level the playing field in the production of global knowledge, we need to understand the practical implications of colonial heritage and how it has disproportionately affected scientific discourse and the generation and utilization of scientific knowledge from and about the Global South. This article explores how research practitioners can level the playing field. We must think about how we can collectively change the narrative so that every emerging scientist from the Global South can flourish and have an equal opportunity to conduct research that is meaningful to them and their societies. We argue the time has come for innovative and flexible models allowing science diplomacy to integrate features of reflexive and inclusive governance in its very core structures.